2015
DOI: 10.1007/978-1-4939-2288-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Targeting of Catalytic RNAs

Abstract: Genetic transformation of mitochondria in multicellular eukaryotes has remained inaccessible, hindering fundamental investigations and applications to gene therapy or biotechnology. In this context, we have developed a strategy to target nuclear transgene-encoded RNAs into mitochondria in plants. We describe here mitochondrial targeting of trans-cleaving ribozymes destined to knockdown organelle RNAs for regulation studies and inverse genetics and biotechnological purposes. The design and functional assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Gómez & Pallás (2010a, b) had shown that a ncRNA with defined secondary structure is able to mediate functional foreign mRNA targeting into plastids. Mitochondrial biogenesis and metabolism can be also influenced by the expression of artificial miRNAs against mRNAs encoding important mitochondrial enzymes (Haas et al, 2008;Stoll et al, 2014) or chimeric ribozymes for directed knockdown of mtRNA, leading to a genetic manipulation of plant mitochondria (Val et al, 2011;Mileshina et al, 2015). How such transplastomic/transmitochondrial manipulations could affect plant organellar stress response under the field conditions?…”
Section: Further Perspectives and Conclusionmentioning
confidence: 99%
“…Gómez & Pallás (2010a, b) had shown that a ncRNA with defined secondary structure is able to mediate functional foreign mRNA targeting into plastids. Mitochondrial biogenesis and metabolism can be also influenced by the expression of artificial miRNAs against mRNAs encoding important mitochondrial enzymes (Haas et al, 2008;Stoll et al, 2014) or chimeric ribozymes for directed knockdown of mtRNA, leading to a genetic manipulation of plant mitochondria (Val et al, 2011;Mileshina et al, 2015). How such transplastomic/transmitochondrial manipulations could affect plant organellar stress response under the field conditions?…”
Section: Further Perspectives and Conclusionmentioning
confidence: 99%